On the Structural and Vibrational Properties of Solid Endohedral Metallofullerene Li@C60 - Vrankić, Martina; Nakagawa, Takeshi; Menelaou, Melita; Takabayashi, Yasuhiro; Yoshikane, Naoya; Matsui, Keisuke; Kokubo, Ken; Kato, Kenichi; Kawaguchi-Imada, Saori; Kadobayashi, Hirokazu; Arvanitidis, John; Kubota, Yoshiki; et al. (My University, 2024)
The endohedral lithium fulleride, Li+@C60•−, is a potential precursor for new families of molecular superconducting and electronic materials beyond those accessible to date from C60 itself. Solid Li@C60 comprises (Li@C60)2 dimers, isostructural and isoelectronic with the (C59N)2 units found in solid azafullerene. Here, we investigate the structural and vibrational properties of Li@C60 samples synthesized by electrolytic reduction routes. The resulting materials are of high quality, with crystallinity far superior to that of their antecedents isolated by chemical reduction. They permit facile, unambiguous identification of both the reduced state of the fulleride units and the interball C-C bonds responsible for dimerization. However, severe orientational disorder conceals any crystal symmetry lowering due to the presence of dimers. Diffraction reveals the adoption of a hexagonal crystal structure (space group P63/mmc) at both low temperatures and high pressures, typically associated with close-packing of spherical monomer units. Such a situation is reminiscent of the structural behavior of the high-pressure Phase I of solid dihydrogen, H2.
Keywords: dimerization; endofullerenes; high pressure; synchrotron X-ray diffraction; vibrational spectroscopy